(untitled) (Fiep Bulletin - online, 2013)
The aging population has been the subject of attention in Brazil, once there is a significant increase in the number of elderly in the population. It is observed that along with this demographic transition, this population needs surgery and therapeutic treatments, which are increasing the demand for blood and its components. The study aims to characterize the use of blood products by the elderly population of a university hospital. Methodology: This was a retrospective and descriptive study with data held in HUOL / UFRN / Natal, from January to June 2008. Result: Of 773 requests for blood, 324 (41.9%) are intended for elderly, 35.5% of those aged 60 to 69 years and 64.4% with more than 70 years, 30.9% female and of 69.1% male. Regarding the sector, 37.7% happened in medical clinic, 31.8% in surgical clinic, and 29.3% in ICU. Regarding the type of transfusion, 54.3% were of urgency, the concentrate of red blood cells the most common, with 222 (68.5%), and 60.8% of those surveyed were multitransfused. Conclusion: This study found that there is an increase in the use o